An online browser-based attentional blink replication using visual objects - Sharabas, Deena; Varlet, Manuel; Grootswagers, Tijl (PloS one, 2023)
The complex relationship between attention and visual perception can be exemplified and investigated through the Attentional Blink. The attentional blink is characterised by impaired attention to the second of two target stimuli, when both occur within 200 – 500ms. The attentional blink has been well studied in experimental lab settings. However, despite the rise of online methods for behavioural research, their suitability for studying the attentional blink has not been fully addressed yet, the main concern being the lack of control and timing variability for stimulus presentation. Here, we investigated the suitability of online testing for studying the attentional blink with visual objects. Our results show a clear attentional blink effect between 200 to 400ms following the distractor including a Lag 1 sparing effect in line with previous research despite significant inter-subject and timing variability. This work demonstrates the suitability of online methods for studying the attentional blink with visual objects, opening new avenues to explore its underlying processes.